1994
DOI: 10.1247/csf.19.201
|View full text |Cite
|
Sign up to set email alerts
|

GDP Inhibits the Activity of the Centrosome to Nucleate Microtubules.

Abstract: ABSTRACT. Microtubule-nucleating ability of the centrosome in the isolated mitotic apparatus was investigated under the condition that the centrosomal fragment was preincubated with guanine nucleotides or its derivatives. GTPand non-hydrolyzable GTP analogues such as GTP-fS or GMP-PNPconsistently supported high activity of the centrosome to nucleate microtubules. On the other hand, GDPsubstantially suppressed the microtubule-nucleating activity of the centrosomes. Evidence has been presented that this is not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This may be why Figure 5 shows a weaker inhibition by GTP-γS than GDP. In a previous study (Nakazawa et al, 1994), the number of asters was not clearly distinguishable among assembly systems containing GTP, GTP-γS, or GMP-PNP. Therefore, the inhibition of the MtSt formation by GTP-γS in the present study would suggest that the inhibition was due not to the Mt nucleation but to the Mt growth.…”
Section: Turbidimetric Analyses Of the Bead-directed Assembly Systemmentioning
confidence: 62%
See 4 more Smart Citations
“…This may be why Figure 5 shows a weaker inhibition by GTP-γS than GDP. In a previous study (Nakazawa et al, 1994), the number of asters was not clearly distinguishable among assembly systems containing GTP, GTP-γS, or GMP-PNP. Therefore, the inhibition of the MtSt formation by GTP-γS in the present study would suggest that the inhibition was due not to the Mt nucleation but to the Mt growth.…”
Section: Turbidimetric Analyses Of the Bead-directed Assembly Systemmentioning
confidence: 62%
“…The effect of GDP on the aster forming activity of MTOGs was preliminarily examined by Ohta et al (1989), who found that the aster formation was inhibited when p51 was saturated with GDP, and recently that p51 has a Kd of 1.1 µM for GTP and 0.15 µM for GDP (Ohta et al, 1999). That Mt assembly is inhibited by GDP-saturated p51 was later confirmed by Nakazawa et al (1994).…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations